2011
DOI: 10.3109/03009742.2011.605390
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, prevalence, and consultation rates of shoulder complaints in general practice

Abstract: Although the incidence of shoulder complaints in general practice is as high as 29.3 per 1000 person-years, GPs' workload is generally low, as nearly half of these patients consult their GP only once for their complaint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
114
1
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(133 citation statements)
references
References 20 publications
4
114
1
11
Order By: Relevance
“…Epub 26 Mar 2015. doi:10.2519/jospt.2015 T t KEY WORDS: mobilization, physical therapy, shoulder impingement syndrome, shoulder pain S houlder pain is highly prevalent and among mus culoskeletal disorders is the third most common reason for visiting a primary care physician. 16,33,46 As many as two thirds of people who have shoulder complaints receive a diagnosis of rotator cuff (RC) tendinopathy. 46 Rotator cuff tendinopathy often leads to decreased function, 34 lower health related quality of life, 34 poor sleep quality, 47 and work absenteeism.…”
Section: T T Level Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Epub 26 Mar 2015. doi:10.2519/jospt.2015 T t KEY WORDS: mobilization, physical therapy, shoulder impingement syndrome, shoulder pain S houlder pain is highly prevalent and among mus culoskeletal disorders is the third most common reason for visiting a primary care physician. 16,33,46 As many as two thirds of people who have shoulder complaints receive a diagnosis of rotator cuff (RC) tendinopathy. 46 Rotator cuff tendinopathy often leads to decreased function, 34 lower health related quality of life, 34 poor sleep quality, 47 and work absenteeism.…”
Section: T T Level Of Evidencementioning
confidence: 99%
“…16,33,46 As many as two thirds of people who have shoulder complaints receive a diagnosis of rotator cuff (RC) tendinopathy. 46 Rotator cuff tendinopathy often leads to decreased function, 34 lower health related quality of life, 34 poor sleep quality, 47 and work absenteeism.…”
mentioning
confidence: 99%
“…Studies from the industrialized nations indicated that SP constituted a tremendous burden on the healthcare system [7,20,31] particularly primary and secondary health care facilities. The main focus of the present study was to investigate the frequency of referral and pattern of management of patients with problem of SP seen over a five year period in a physiotherapy department of a tertiary hospital.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence is higher in women and in people aged over 45 years (1) . The most frequent cause of shoulder pain is subacromial impingement syndrome (SIS) (2) which is caused by compression of the rotator cuff, long head of the biceps tendon, and subacromial bursa between the humerus and coracoacromial arch as a result of an intrinsic or an extrinsic mechanism (3) .…”
Section: P Atıcı öZtürk Et Al Effectiveness Of Low-level Laser Thermentioning
confidence: 99%